The Effect of Organizational Support on Employee Loyalty at PT Permodalan Nasional Madani Medan Branch - Satria B, Benny; Erwansyah; Hernawaty (International Conference Epicentrum of Economic Global Framework, 2025)
This study aims to analyze the effect of organizational support on employee loyalty at PT Permodalan Nasional Madani Medan Branch. Organizational support is considered an important factor in improving employee commitment, emotional attachment, and willingness to remain within the organization. This research employed a quantitative approach with an explanatory research design. The population in this study consisted of all employees of PT Permodalan Nasional Madani Medan Branch, with a total sample of 50 respondents selected using the census sampling technique. Data were collected through questionnaires and analyzed using descriptive statistics, reliability testing, and simple linear regression analysis with the assistance of Jamovi software. The results showed that organizational support had a positive and significant effect on employee loyalty. The regression analysis indicated a significance value of 0.000, which was lower than 0.05, meaning that the proposed hypothesis was accepted. In addition, the coefficient of determination test showed that organizational support explained 50.4% of the variation in employee loyalty, while the remaining 49.6% was influenced by other variables outside this study. These findings indicate that employees who perceive stronger organizational support tend to demonstrate higher loyalty toward the organization. This study concludes that organizational support plays an important role in strengthening employee loyalty at PT Permodalan Nasional Madani Medan Branch. Therefore, organizations are expected to continuously improve supportive organizational practices, including employee appreciation, welfare concern, and fair organizational policies, in order to maintain employee commitment and organizational sustainability.